CRF-Seq and CRF-DepTree at PARSEME Shared Task 2018: Detecting Verbal MWEs using Sequential and Dependency-Based Approaches - Vogel, Carl; Maldonado Guerra, Alfredo; Moreau, Erwan (Association for Computational Linguistics, 2018)
This paper describes two systems for detecting Verbal Multiword Expressions (VMWEs) which both competed in the closed track at the PARSEME VMWE Shared Task 2018. CRF-DepTree- categs implements an approach based on the dependency tree, intended to exploit the syntac- tic and semantic relations between tokens; CRF-Seq-nocategs implements a robust sequential method which requires only lemmas and morphosyntactic tags. Both systems ranked in the top half of the ranking, the latter ranking second for token-based evaluation. The code for both systems is published under the GNU General Public License version 3.0 1 and is available at http://github.com/erwanm/adapt-vmwe18.
Proceedings of the Joint Workshop on Linguistic Annotation, Multiword Expressions and Constructions (LAW-MWE-CxG-2018)
PUBLISHED
Sante Fe, NM, USA
Keywords: Digital Humanities; Computational Linguistics; multi-word expressions